Leadership Skills of Administrators of Divine Word Colleges in Region I, Philippines as Perceived by the Employees and Employees’ Work Engagement - Abun, Damianus; Tabur, Mirriam; Agoot, Frederick (IJRDO - Journal of Applied Management Science, 2017)
The study was to measure the level of leadership skills of administrators/managers of Divine Word Colleges in Region I and how leadership skills affect the work engagement of employees. In order to carry out the study, the theory of leadership was formulated. Related literature and studies were reviewed to support the theoretical foundation of the study. Since the study was a quantitative study, questionnaires were used to gather the data and the questionnaires were adopted from Foronda (2010). Pearson r was used to determine the relationship between leadership skills of administrators and work engagement of employees. The study found that the leadership skills of administrators/managers are within the level of “Good” or “High” and leadership skills correlate to the work engagement of employees. Leadership skills affect the work engagement of employees. The higher the leadership skills are, the higher the work engagement becomes. Thus the hypothesis of the study is rejected